Processing, visualization and analysis of 3D confocal microscopic images - Guan, Yunqing (2008)
Confocal laser scanning microscopes have been widely employed in biology research for many years. The advancement of computer technology enables interactive visualization and quantitative analysis of volumetric confocal image datasets thus giving deep insights into cellular structures. This thesis details the computer techniques developed by the author to facilitate 3D confocal image studies. The key contributions of this work are in (1) confocal image acquisition and management, (2) 3D image processing, and (3) Virtual Reality (VR) enhanced visualization and analysis of cellular structures.